Strategic Approach of Managing Key Performance Indicators for Outstanding Business Performance - Abd Rahman Ahmad; Lim Chen Bin (Communications of International Proceedings, 2020)
In today’s economic environment, performance measurement is important for industries to grow especially for SMEs in order to sustain in the global market. This study is focused on the Malaysian SMEs’ strategic approach to managing KPIs for their business performance. The strategic approach here is looking at business strategy, communication method and monitoring approach that support for the internal business processes with the development of KPIs. This study is based on a quantitative approach where the survey questionnaires were distributed among SMEs in Malaysia. The findings show that most of the SMEs put more attention to measuring the financial and customer perspective performances. In addition, the strategic approach includes the business strategy, communication method and monitoring tool that are implemented to manage the related business performance. Moreover, the finding also shows that SMEs lack of attentiveness on the monitoring and evaluation of a real time-factor KPIs. Communication among staff within the organization was found that had a significant relationship with managing the SMEs’ business performance. In this study, communication methods implemented by SMEs are at a moderate level. The management has clarified the KPIs in the company and all employees understood the proposed KPIs.
Keywords: Key Performance Indicators; Small and Medium Enterprises; Strategic Planning.